Assessment of Polder System Drainage Experimentation Performance Related to Tidal Floods in Mulyorejo, Pekalongan, Indonesia - Wahyudi, Slamet Imam (International Journal of Integrated Engineering, 2019)
During the last 20 years, Pekalongan was flooded by tides and rainfall, this had a big impact on the Mulyorejo area as a pilot project. There were a lot of rice fields that turned into salty fishponds. The land is located below the sea and river water level. The objectives of the research are to assess a temporary polder infrastructure, to analyse the in-out flow and its water balance. The research knows different stages of the investigation and data collection that contains water system analysis. Mulyorejo has a catchment area of 1,841,148 m2 (184 ha) that contains houses, batik industry, offices, schools, agriculture and aquaculture. The polder system has different inlets i.e. Meduri river, rainfall, southern canal and there are water outlets like pumps and evapotranspiration. To design for t=25 year rainfall return periods of 187,797 m3/hour and to analyse a water balance. The area has a large surplus of 186,950 m3/hour water. The method ‘Bakken model’ is used to visualize the different waterways, inlet and outlet and retention areas. The pond will secure a retention capacity of 37,372 m³. Also, a new pump house will drain water into the Sengkarang river instead of Meduri river.